Looking for subsurface features: the role of geophysical research in the revitalization of the Palace and Park Complex in Rzuchów, Poland - Mackiewicz Ewa; Mendecki Maciej J.; Pierwoła Jolanta; Żogała Bogdan; Nawrocki Dariusz; Paszczyński Aleksander; Myga-Piątek Urszula (Environmental & Socio-economic Studies)
This article discusses the significance of geophysical research in the context of historical renewal, emphasizing its contributions to risk assessment, sustainable redevelopment, and non-uniqueness in geophysical interpretation. The geophysical studies were conducted in the surroundings of the Palace of Rzuchów, timing to locate the modern infrastructure, historical objects, and other environmental elements that can either threaten the renewal process or add value to the historical heritage. We used three geophysical methods to study the palace surroundings: frequency domain electromagnetics, magnetometry, and electrical resistivity tomography. The findings revealed significant anomalies corresponding to buried modern infrastructure and historical artifacts, offering critical insights for preserving cultural heritage while planning sustainable redevelopment, thus demonstrating the practical utility of integrating geophysical methods in complex historical and environmental contexts.